2017
DOI: 10.1016/j.psychsport.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Empowering youth sport and acculturation: Examining the hosts’ perspective in Greek adolescents

Abstract: Usage of any items from the University of Cumbria's institutional repository 'Insight' must conform to the following fair usage guidelines. Any item and its associated metadata held in the University of Cumbria's institutional repository Insight (unless stated otherwise on the metadata record) may be copied, displayed or performed, and stored in line with the JISC fair dealing guidelines (available here) for educational and notforprofit activities provided that • the authors, title and full bibliographic detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
1
8
0
3
Order By: Relevance
“…Se observó que la puntuación media más alta fue para la satisfacción de la necesidad de autonomía-volición, al igual que en otros estudios realizados con el BNSSS (Morela, et al, 2017;Ng, et al, 2011). Sin embargo, otros autores que seguían una visión tridimensional de las necesidades (Balaguer, Castillo y Duda, 2008;Sarrazin, Vallerand, Guillet, Pelletier y Cury, 2002) afirmaron la supremacía de la satisfacción de la necesidad de autonomía sobre el resto de necesidades, por estar más relacionada directamente con la motivación intrínseca.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Se observó que la puntuación media más alta fue para la satisfacción de la necesidad de autonomía-volición, al igual que en otros estudios realizados con el BNSSS (Morela, et al, 2017;Ng, et al, 2011). Sin embargo, otros autores que seguían una visión tridimensional de las necesidades (Balaguer, Castillo y Duda, 2008;Sarrazin, Vallerand, Guillet, Pelletier y Cury, 2002) afirmaron la supremacía de la satisfacción de la necesidad de autonomía sobre el resto de necesidades, por estar más relacionada directamente con la motivación intrínseca.…”
Section: Discussionunclassified
“…Actualmente, en el ámbito deportivo, los estudios realizados con el BNSSS están enfocados a relacionar las necesidades psicológicas básicas con diversas variables poco relacionadas con características demográficas o deportivas, como son: engagement y antipatía (Curran, Hill y Niemic, 2013;Curran, Hill, Hall y Jowett, 2014;Curran, Hill, Ntoumanis, Hall y Jowett, 2016); experiencia, diálogo interno y estado de flow (Delrue, Mouratidis, Haerens, de Muynck, Aelterman y Vansteenkiste, 2016); clima motivacional (Hodge y Gucciardi, 2015;Morela, Hatzigeorgiadis, Sanchez, Papaioannou y Elbe, 2017), autoridad del entrenador (Brinton, Hill y Ward, 2017); bienestar, metas de logro y conducta del entrenador (Healy, Ntoumanis, van Zanten y Paine, 2014;Pope y Wilson, 2014); perfeccionismo, burnout y engagement ; liderazgo y bienestar (Stenling y Tafvelin, 2014, Stenling, Lindwall y Hassmén, 2015; y, burnout (Li, Wang y Pyun , 2017), entre otros.…”
unclassified
“…Finally, in a study examining the hosts’ perspectives, Morela et al. (2017) found that an empowering motivational climate, characterized as mastery‐oriented and supportive of the needs of autonomy, competence, and relatedness, was positively associated with multiculturalism attitudes, that is, attitudes favoring both migrants’ maintenance of their culture and their interaction with the host culture. Building upon the results of the previous study (Morela et al., 2017), in which an empowering motivational climate was linked to positive multiculturalism attitudes among Greek adolescent athletes, the present study aimed to explore the role of prosocial skills, as potential mediators of the relationship between an empowering motivational climate and multiculturalism attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Morela et al. (2017) found that Greek adolescents participating in organized sport scored higher on attitudes toward multicultural contact compared to those who did not participate in sports. In addition, an empowering motivational climate, characterized by a mastery climate and supportive of athletes’ needs for competence, autonomy, and relatedness, was positively linked to multiculturalism attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…El deporte escolar y los valores transmitidos por el mismo siempre ha sido un tema clásico en los estudios sobre deporte, cultura y sociedad. La socialización deportiva y en valores desarrollada en Grecia es la línea de investigación ofrecida por un grupo de investigadores que centra su interés en la socialización de población migrante (Morela et al, 2017). Para ellos, la socialización deportiva es un proceso bidireccional que involucra tanto a la población migrante como a la de acogida.…”
Section: Meta-análisis De Los Temas Clásicosunclassified